Analysing the customer perspective in relation to supermarkets in the UK moving toward hybrid competitive strategies - Pirzada, Amna (2017)
The topic of competitive advantage has received much exploration from strategy theorists since the 20th century due to corporations wishing to distinguish themselves from rivals through the value propositions offered to customers. With much of the theory proposing competitive advantage will be achieved either through cost-leadership or differentiation, extensive research has been conducted in to this matter to determine whether strategic purity translates in to higher performance. While much research exists on this topic, there is a lack of research concerning the customer perception toward the pursue of hybrid strategies, as opposed to strategic purity. The supermarket industry in the U.K is the prime focus of this dissertation, due to the nature of the competition not only being vigorous, but also the result of supermarkets following different strategies, as proposed by the literature, to achieve competitive advantage. As the nature of the competition in this industry continues to intensify, a matter which is largely the result of the rise of the discount retailers following the strategy of cost- leadership – with key players being Aldi and Lidl - the importance of sustaining an established advantage is vital for the increase of market share. As a way to combat combination, supermarket in the UK have been moving closer to features of hybrid strategies, a notion which is strongly argued against by theory. Undertaking an industry analysis through descriptive studies will highlight key industrial trends which reflect erosion of strategic purity for Tesco, Sainsbury’s and Lidl. Rather than investigating whether supermarkets which adhere to the predictions of the literature that dictates following a single generic strategy as proposed by Porter will result in advantage, the core aim of this dissertation is to examine the customer perspective in relation to supermarkets in the UK moving away from their established strategic positions through combining aspects of both product differentiation and low-cost. This has been done through conducting empirical research via online surveys and semi-structured phone interviews. 4 It is hoped that undertaking this dissertation will also shed substantial light on the axioms which have dictated much of the strategy literature including the perceived trade-off between cost leadership and differentiation, and whether the most influential theories, like that of Michael Porter’s still uphold when being applied to firms competing in the competitive supermarket industry.